MAKNA DAN FENOMENA PERILAKU PENGGUNA PERPUSTAKAAN DI ERA DIGITAL - Liliek Soetjiatie; Suhartini .; I Dewa Gede Hari Wisana (JURNAL PENELITIAN KESEHATAN, 2014)
There is a phenomenon that the development of the modern world in which the library of knowledge ml or recorder recorded knowledge stored in books or libraries with wall changes its function as a virtual library presence on line. Ml of research is descriptive research, which aims to get an idea of the meaning of the library to the user (user ) library, virtual library user behavior change and the ideal library. As the population in this research is all polytechnic students Surabaya, while the sample or informants come and elektromedik Engineering Program , Dental Nursing , Nursing and Midwifery Health Polteknik Surabaya is located in the campus environment. Informants were taken by purposive sampling technique. Analysis of the data using a phenomenological perspective, where the meaning of subjective and behavioral generate any inter subjective interpretation of an event given by each informant . Concluding this research is : a process of formation of system relevance in the process of social interaction. That individuals in this research is to determine the behavior of the students actions as humans living in the modern era have freedom including the use of the library, not lost in the euphoria of the virtual world that promises a wealth of information with electronic capabilities possessed, but still need a conventional library has its advantages and different angles. Keywords: User libraries , meaning , the phenomenon , the Virtual Library .